Peranan Model Pembelajaran Numbered Head Together (NHT) Terhadap Motivasi Belajar IPA di SD - Putri Novi Sa'idah; Aulia Nur Faizah; Zuyyina isnaina (JURNAL PEDAGOGIK PENDIDIKAN DASAR, 2022)
Number Head Together (NHT) provides opportunities for students to exchange ideas and consider answers with the syntax of playing and discussing. This study aims to determine the results of students’ motivation in participating in science learning using the Number Head Together (NHT) learning model. The research method used is a literature study. The form of motivation that can be carried out in learning activities is fostering healthy competition. The NHT learning model is a learning model that can attract students' interest and learning motivation